The Guidelines for Change for Sustainable Business Development Based on ESG Principles - Mathuros, Suwimon; Teerarujikajohndej, Juntima; Chuenchum, Yada (Interdisciplinary Academic and Research Journal, 2023)
With the changes in various aspects of the environment in modern times, as a result, business operators need to drive sustainable development goals by using various concepts. The concepts that are widely accepted in the present era for sustainability are the ESG concepts, which It is concepts that investors use when making investment decisions. It will give importance to doing business concerning 3 main responsibilities: the environment (Environment), society (Social), and governance (Governance). Social is a criterion that measures how businesses manage relationships and communicate with customers. raw material suppliers, customers, or stakeholders? and governance is criteria that measure how a business manages its governance relationship services. for efficient, transparent, verifiable management of stakeholders. In this article, the author would like to present the concept and principles of sustainable development. The concepts and principles of ESG, perspectives, and results of sustainable development. and change guidelines for sustainable business development according to ESG principles so that business operators will be able to apply the information presented by the author in this article as a guideline for developing and improving work processes to achieve business sustainability, continue both now and in the future.